“Padrões e desvios”: racismo estrutural e controle social da pobreza no acolhimento institucional de crianças e adolescentes na cidade de São Paulo - Quadros, Leonice Fazola de (2025)
This dissertation investigates how structural racism and institutional practices of social control of poverty materialize in records concerning the homes of Black, poor, and mothering women in the city of São Paulo between 2010 and 2020. The research is based on an analysis of the recent history of judicial processes related to the institutional reception of children and adolescents. In the first chapter, the focus is on the subjects: the history of the “10 Marias,” state agents, and myself. The Marias tell the stories of women whose trajectories were recorded in my field diary over nearly 15 years of work at the São Paulo State Public Defender’s Office. But their lives do not unfold in a vacuum. The space they inhabit—the favela—is not merely a backdrop but an essential part of how they live and resist. The territory shapes their relationships, their opportunities, and their challenges. Thus, the second chapter addresses the inventory of absence and territory, as the favela is not just a geographic location but also a space of disputes and narrative construction. The Água Vermelha favela is the setting I chose for affective reasons, a place where my life intertwines with theirs once again—no longer as a professional but as a favelada myself. In this inventory of absence, the structural mechanisms that perpetuate historical cycles of exclusion become evident. In the third chapter, the bathroom, as both a physical and symbolic space, emerges as a key element in the construction of discourses. The research weaves together historical, social, and spatial dimensions to demonstrate that the bathroom, far from being a banal space, is a political field loaded with social and symbolic meanings. The fourth chapter discusses dirt, disorder, and morality, which serve to justify practices of surveillance and control over Black, poor, and peripheral bodies. The State exercises its surveillance through agents who become intermediaries in the disciplining of bodies, imposing punishments that are not physical but erode self-esteem and any possibility of physical and mental restructuring. These individuals are subjected to multiple layers of violence from birth. Records, therefore, are the materialization of this control and play a central role in constructing ideas of deviation and standards, reinforcing moralist and hygienist discourses through racialized readings of what is dirty or clean, organized or disorganized, appropriate or inappropriate, dangerous or harmless. Engaging with urban studies, social theory, and cultural history, this interdisciplinary—though historically grounded—dissertation articulates concepts and methodologies that help to understand how discourses on dirt and disorder function as devices of racial exclusion, eugenics, and the criminalization of poverty. Throughout the chapters, the research seeks to unveil how these practices inscribe themselves into the daily lives of the Marias in the city of São Paulo